Cooperative Learning Strategies and their Impact on the Promotion of Editorial Expression Students of the Department of Arabic Language Teaching at the Islamic University of Tulung Agung/استراتيجيات التعلّم التعاوني وأثرها في ترقية التعبير التحريري لدى طلبة قسم تعليم للغة العربية بالجامعة الإسلامية الحكومية تولونج أجونج - luthfi Abdul Manaf (JURNAL IJ-ATL, 2017)
The aim of this research is to identify cooperative learning strategies in enhancing the skill of written expression and understanding the impact of these strategies. The introduction of collaborative learning in the promotion of the skill of written expression among students at the Department of Arabic Language Education at the Islamic University of Tolong Agung. Use this search descriptive qualitative portal. The researcher also used research tools to collect data, namely observation, interview and documents. Data analysis is data reduction, data presentation, and data validation by constant comparison. To examine the validity of the data, the researcher is working to prolong the times of attendance and tripartite and discuss with some of the brothers.The results of this research showed that the goals of teaching expression in the cooperative learning strategy are using steps such as the teacher to set goals, materials and teaching methods and then set the procedures of education by dividing the students into six groups. The teacher prepares the working drawings for the students with different colors for each group, distributed to each group. A student from the groups began working by walking around the teacher to observe the positive tingling atmosphere. After the students finished working, each group discussed their work in front of another group, and then the teacher evaluated the students' work. The use of cooperative learning strategies has a significant impact on students' skill upgrading in the expression of discretion.يهدف هذا البحث إلى معرفة إستراتيجات التعلم التعاوني في ترقية مهارة التعبير التحريري ومعرفة أثر تلك الاستراتيجات مدخل التعلم التعاوني في ترقية مهارة التعبير التحريري لدى طلبة لدى قسم التربية للغة العربية بالجامعة الإسلامية الحكومية تولونج أجونج. استخدم هذا البحث المدخل الوصفي الكيفي. كما استخدم الباحث أدوات البحث لجمع البيانات وهي الملاحظة والمقابلة والوثائق. وأما تحليل البينات فهو تنقيص البيانات، وتقديم البيانات، واثبات البيانات بمقارنة الثابت. ولتفتيش صحة البيانات يعمل الباحث تطويل أوقات الحضور والتثليثي والمناقشة مع بعض الإخوان.ودلت نتائج هذا البحث على أن أهداف التعليم التعبير التحريري باستراتيجية التعلم التعاوني تستخدم الخطوات منها تعيين المعلم الأهداف والمواد ووسائل التعليمية ثم تعيين إجراءات التعليم بتقسيم الطلبة في ست مجموعات، فيعد المعلم قراطيس العمل للطلبة مع ألوان مختلفة لكل مجموعة، فيوزعها على كل مجموعة. بدأ طالب من المجموعات بالعمل فيتجول المعلم لمراقبة جو التلعم الإيجابي. بعد أن انتهى الطلبة من العمل، قامت كل مجموعة بالمناقشة حول عملهم أمام مجموعة أخرى، ثم بعد ذلك قام المعلم بالتقويم على أعمال الطلبة. واستخدام استراتيجيات التعلم التعاوني له أثر كبير عند الطلبة في ترقية المهارة التعبير التحريري.